Implementasi Koneksi Internet of Things (IoT) Pada Arduino Menggunakan Modul ESP8266 - Muhamad Hilmansyah Susanta; Nana Sujana (Jurnal Teknologi Komputer dan Informatika, 2026)
This study aims to implement an Internet of Things (IoT) system using an Arduino Uno integrated with an ESP8266 module as a network communication interface. The system is designed to enable remote control of electronic devices, particularly an LED, through an internet-based application. In this system, Arduino functions as the main data processing unit, while the ESP8266 module serves as a bridge connecting the system to a WiFi network. The research method includes hardware design, software development, and system testing, which covers WiFi connectivity, serial communication, output control, and system response. The testing results show that the ESP8266 module can connect to the WiFi network consistently with a 100% success rate and an average connection time of approximately 4.9 seconds. In addition, data communication between Arduino and ESP8266 operates properly, allowing the system to respond to user commands accurately and in real time. Based on these results, the developed system demonstrates stable and responsive performance, making it suitable for educational purposes as well as basic IoT implementation using Arduino